2017
DOI: 10.1038/s41598-017-01961-4
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a cytochrome P450 and a UDP-glycosyltransferase is associated with imidacloprid resistance in the Colorado potato beetle, Leptinotarsa decemlineata

Abstract: Current control of insect pests relies on chemical insecticides, however, insecticide resistance development by pests is a growing concern in pest management. The main mechanisms for insecticide resistance typically involve elevated activity of detoxifying enzymes and xenobiotic transporters that break-down and excrete insecticide molecules. In this study, we investigated the molecular mechanisms of imidacloprid resistance in the Colorado potato beetle, Leptinotarsa decemlineata (Say) (Coleoptera: Chrysomelida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
89
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 63 publications
3
89
2
2
Order By: Relevance
“…LdGST-e2a, LdGST-e2b, LdGST-o5 and LdGST-t1 were significantly overexpressed in Leptinotarsa decemlineata after exposure to the insecticides fipronil, endosulfan or cyhalothrin (Han et al, 2016). In addition, there are many papers about the mechanism of resistance to imidacloprid that indicate that P450s are involved in this mechanism (Karunker et al, 2008;Bao et al, 2016;Pang et al, 2016;Zhang et al, 2016;Kaplanoglu et al, 2017). For example, a P450 gene (CYP6ER1) was found to be associated with imidacloprid resistance in N. lugens (Pang et al, 2016); Similarly, CYP6CM1 was found to be important in imidacloprid resistance in both B. tabaci MED and MEAM1 (Karunker et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…LdGST-e2a, LdGST-e2b, LdGST-o5 and LdGST-t1 were significantly overexpressed in Leptinotarsa decemlineata after exposure to the insecticides fipronil, endosulfan or cyhalothrin (Han et al, 2016). In addition, there are many papers about the mechanism of resistance to imidacloprid that indicate that P450s are involved in this mechanism (Karunker et al, 2008;Bao et al, 2016;Pang et al, 2016;Zhang et al, 2016;Kaplanoglu et al, 2017). For example, a P450 gene (CYP6ER1) was found to be associated with imidacloprid resistance in N. lugens (Pang et al, 2016); Similarly, CYP6CM1 was found to be important in imidacloprid resistance in both B. tabaci MED and MEAM1 (Karunker et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] More importantly, transcriptional overexpression of P450 genes and the corresponding enhanced metabolic ability are often found in insecticide-resistant populations, and this appears to be a common phenomenon in the evolution of resistance. [9][10][11][12] For example, overexpression of CYP4Q3 contributes to imidacloprid resistance in a Colorado potato beetle Leptinotarsa decemlineata resistant strain, 13 and overexpression of cytochrome P450 CYP6CM1 is linked to high resistance to imidacloprid in the B and Q biotypes of Bemisia tabaci (Hemiptera: Aleyrodidae). 14 Expression of CYP9M10 was 260-fold higher in a permethrin-resistant Culex quinquefasciatus strain, compared with the susceptible strain.…”
Section: Introductionmentioning
confidence: 99%
“…In insect, UGTs commonly catalyze conjugation of small lipophilic substrates with UDP‐glucose, playing an important role in detoxification and homeostatic function . The overexpression of UGT genes in insecticide‐resistant insects has been reported in Leptinotarsa decemlineata (Say), Plutella xylostella (L.) Diaphorina citri Kuwayama, Tetranychus cinnabarinus (Boisduval), and Anopheles sinensis Wiedemann . It has been reported that UGTs were induced by insecticide exposures in Spodoptera exigua (HĂŒbner) and Bemisia tabaci (Gennadius) …”
Section: Introductionmentioning
confidence: 99%
“…11,12 The overexpression of UGT genes in insecticide-resistant insects has been reported in Leptinotarsa decemlineata (Say), Plutella xylostella (L.) Diaphorina citri Kuwayama, Tetranychus cinnabarinus (Boisduval), and Anopheles sinensis Wiedemann. [13][14][15][16][17] It has been reported that UGTs were induced by insecticide exposures in Spodoptera exigua (HĂŒbner) and Bemisia tabaci (Gennadius). 18,19 www.soci.org X Chen et al…”
Section: Introductionmentioning
confidence: 99%